Vacas a matar. De la dicotomía soberana al umbral biopolítico en ficciones ganaderas del Cono Sur. (Altre Modernità, 2021)
Animality, a knot of tension between biological life and historicity, runs through the series of slaughterhouses that Argentine critics have investigated as sovereign fiction, guided by political dualism. The 1840 polarization embodied in Echeverría´s El matadero (The Slaughterhouse), with narrative hesitations about voices and animalized bodies of popular sector, has returned since the middle of the 20th century in versions of the civilization-barbarity dichotomy, which maintain the nature-culture distinction and the coordinates of anthropocentric historicity, such as Walsh's chronicle that in 1967 amends the class distribution of Echeverría. The critical threshold of life (Agamben) emerges in recent rewritings of the slaughterhouse, where the flow of capital passes through not only the body of the worker but also the living being. A story by Kohan (2009) and a novel by Maia (2013) discover under dichotomy the complexity of passages between animals and humans, where they investigate the economies of relationships between protected and abandoned lives. By confronting Argentine and Brazilian cultural conflicts, both marked by the weight of agro-export economies and dualism as control of mixtures, these stories of cattle workers inquire about the diffuseness of the life-death border after two centuries of humanist progress in Latin America.
Keywords: Bodies; Dualisms; Economies; Life-Death; Work